The Relevance Between Image and Utterance Found in Indonesian Educational Literacy Comics - Claria, Dewa Ayu Kadek (International Seminar on Austronesian Languages and Literature, 2021)
This research tries to analyze the relevance between the image and utterance found in Indonesian educational literacy comics. Both of them have an important role in the process of delivering messages to the readers. The data used in this study are Indonesian literacy comics that contain moral messages for the readers through stories in the form of comics. The method used in this research is the observing method and then the results are written descriptively. The theory used is the relevance theory proposed by Billy Clark (2013). The results of the analysis show that the Indonesian literacy comics used in this research are very relevant. There were metaphors used as utterances in the comics but they did not change the context of the conversation. Other data shows that the utterances conveyed by the speaker obtain an appropriate response so that the communication is in accordance with the context of the desired situation